The Effectiveness of the Implementation of the Marine and Fisheries Business Actor Card (Kusuka) Program for Fisherman in Anaiwoi Village - Yusuf, Rahmi; Nursamsir; A, Nimrah Rahmayanti Yusuf (Teras Kampus, 2025)
This study analyzes the effectiveness of the Fishermen and Fisheries Business Actor Card (KUSUKA) program implemented by the Ministry of Marine Affairs and Fisheries of Indonesia in Anaiwoi Village. The program aims to improve fishermen’s welfare by providing a unified identity for marine and fisheries business actors. Using Campbell’s program effectiveness indicators, this descriptive qualitative research employed observations, interviews, and documentation, with data analysis following the steps of data collection, reduction, presentation, and conclusion drawing. Findings indicate that the program has achieved partial success. Outreach activities have reached most fishermen, yet information dissemination remains uneven. Target achievement shows that while many active fishermen have been registered, administrative understanding and data collection challenges persist. Beneficiaries’ satisfaction is relatively good as the program helps in legalizing fishing businesses; however, complicated assistance procedures and uneven aid distribution limit its perceived benefits. Regarding input-output efficiency, active data collection and local authority involvement have contributed positively, but limitations in staff, facilities, infrastructure, and budget continue to hinder full implementation. Overall, the KUSUKA program has improved fishermen’s access to administrative services and created a more structured database of fisheries business actors. Nevertheless, it has not fully achieved its objectives. Strengthening outreach, streamlining data collection, simplifying administrative processes, and improving resource allocation are essential for optimizing the program’s future impact.